Parents’ Perceptions on Male Teachers in Peruvian Preschool Education - Cruz, Astrid (2021)
Objective. This article aimed to explore parents’ perceptions concerning the low presence of men at the initial level and their teaching practice in these educational spaces. Method. A qualitative and exploratory research approach was used. A semi-structured interview was conducted with fathers and mothers of public and private initial-level educational centers in Lima (Peru). The information was analyzed inductively and classified into categories that responded to the objective of the investigation. Results. The main results that emerged from this process were the following: a) the role of society in the teaching exercise of the initial level; b) the female domain and her maternal role; c) distrust of the relationship between men and the care of young children; and d) the male as a figure of discipline, authority, and play. Discussion. This study introduces dialogues in relation to the link between male and childhood and opens an opportunity for schools to direct their change strategies in order to reduce the male gender gap in this teaching context. It also provides the basis to develop future research on the impact of this group on children and their immediate surroundings, knowing their perceptions as key educational actors.